Dysregulated TP53 Among PTSD Patients Leads to Downregulation of miRNA let-7a and Promotes an Inflammatory Th17 Phenotype - Busbee, Philip B.; Bam, Marpe; Yang, Xiaoming; Abdulla, Osama A.; Zhou, Juhua; Ginsberg, Jay Paul (Jack); Aiello, Allison E.; Uddin, Monica; Nagarkatti, Mitzi; Nagarkatti, Prakash S. (Frontiers in Immunology, 2022)
Post-traumatic stress disorder (PTSD) is a psychiatric disorder and patients diagnosed with PTSD often express other comorbid health issues, particularly autoimmune and inflammatory disorders. Our previous reports investigating peripheral blood mononuclear cells (PBMCs) from PTSD patients showed that these patients exhibit an increased inflammatory T helper (Th) cell phenotype and widespread downregulation of microRNAs (miRNAs), key molecules involved in post-transcriptional gene regulation. A combination of analyzing prior datasets on gene and miRNA expression of PBMCs from PTSD and Control samples, as well as experiments using primary PBMCs collected from human PTSD and Controls blood, was used to evaluate TP53 expression, DNA methylation, and miRNA modulation on Th17 development. In the current report, we note several downregulated miRNAs were linked to tumor protein 53 (TP53), also known as p53. Expression data from PBMCs revealed that compared to Controls, PTSD patients exhibited decreased TP53 which correlated with an increased inflammatory Th17 phenotype. Decreased expression of TP53 in the PTSD population was shown to be associated with an increase in DNA methylation in the TP53 promotor region. Lastly, the most significantly downregulated TP53-associated miRNA, let-7a, was shown to negatively regulate Th17 T cells. Let-7a modulation in activated CD4+ T cells was shown to influence Th17 development and function, via alterations in IL-6 and IL-17 production, respectively. Collectively, these studies reveal that PTSD patients could be susceptible to inflammation by epigenetic dysregulation of TP53, which alters the miRNA profile to favor a proinflammatory Th17 phenotype.